Avaliação da radiação ultravioleta na inativação de microrganismos presentes em óleo diesel - Neves, Andressa Caroline (2018)
The addition of biodiesel in the diesel oil is mandatory since 2008, and until 2018 the percentage who currently is 8% (B8) can reach up to 15% (B15), according to the law n° of 13,263 23/03/2016. But biodiesel is susceptible to degradation by unsaturated bonds and high hygroscopicity. During storage the microbiological degradation may occur, caused by contamination of microorganisms, mainly by the presence of water, where in contact with oxygen, light and temperature, provides a favourable environment for the proliferation of microorganisms, generating the formation of biomass that causes various engine problems. With the reduction of these microorganisms is possible to increase the storage time of commercial diesel, favoring the distribution and marketing in a country, such as Brazil. Some alternatives have been used to circumvent this kind of problem, as is the case with chemical additives, but present a disadvantage, as the rising cost of the final product and the generation of waste. The aim of this study is to identify, quantify and inactivate microorganisms present in diesel oil by using ultraviolet radiation to eliminate and/or reduce microbiological growth. We collected samples of diesel S10 (maximum sulphur content of 10 mg kg -1), from different periods throughout the year. Commercial diesel samples were added in a reactor composed of ultraviolet lamps (40W) and circulation system. The tests were conducted at different times of contact with ultraviolet radiation (from 0 to 360 min), varying the sample volume (40 and 60 L) and the use or non-use of the circulation system. The microorganisms present in the diesel S10 B8 before and afterhtreatment were quantified by the technique of microdrop and absorbance, and identified by genetic sequence. The effect of radiation on physical and chemical properties of fuel was rated by: differentiation, temperature, mass spectrometric specifies the 20°C and kinematic viscosity. The combination of 360 minutes of radiation, with circulation of the system provided a decrease of 1, 50x1010 UFC mL-1 for 3, UFC 33x102 mL-1 in concentration of microorganisms. On the physico-chemical properties of diesel oil, the maximum exposure to radiation caused changes on the physical and chemical aspects. Microorganisms of the genera were identified: Staphylococcus sp.; Clostridium sp.; Enterococcus sp.; Enterobacter SP. and Bacillus sp., which presented high potential for degradation of diesel oil and blends, where after 96 hours of incubation, the samples were oxidized. With this we can conclude that the use of UV radiation as a method for microbiological control inativou and/or decreased the microorganisms present, increasing storage of fuel.